Effects of sorghum particle size on milling characteristics, growth performance, and carcass characteristics in finishing pigs - Paulk, C.B.; Hancock, Joe D.; Fahrenholz, Adam C.; Wilson, J.M.; McKinney, Leland J.; Benhke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 200 finishing pigs (PIC TR4 × 1050; average initial BW of 103.2 lb) were used in a 69-d growth assay to determine the effects of sorghum particle size on growth performance. Pigs were sorted by sex and ancestry and balanced by BW, with 5 pigs per pen and 10 pens per treatment. Treatments were a corn-soybean meal-based control with the corn milled to a target mean particle size of 600 μm, and sorghum diets milled to a target mean particle size of 800, 600, or 400 μm. Actual mean particle sizes were 555 μm for corn, and 724, 573, and 319 μm for sorghum, respectively. Feed and water were offered on an ad libitum basis until the pigs were slaughtered (average final BW of 271 lb) at a commercial abattoir. Reducing sorghum particle size improved (linear, P < 0.01) F/G, and we observed a tendency for decreased (P < 0.06) ADFI. Reducing sorghum particle size from 724 to 319 μm had no effects on HCW, backfat thickness, loin depth, or percentage fat-free lean index (FFLI), but tended to increase (P < 0.06) carcass yield. Pigs fed the sorghum-based diets had no difference in growth performance or carcass characteristics compared with those fed the control diet, except carcass yield, which was numerically greater (P < 0.07) for pigs fed the sorghum-based diets. When using a regression equation, we determined that sorghum must be ground to 513 μm to achieve a F/G equal to that of a corn-based diet, with corn ground to 550 μm. In conclusion, linear improvements in F/G and carcass yield were demonstrated with the reduction of sorghum particle size to 319 μm. In this experiment, sorghum should be ground 42 μm finer than corn to achieve a similar feeding value.
Keywords: Swine; Corn; Particle size; Sorghum; Finishing pig